The Relationship of Oral Mucosal Lesions and Removable Prostheses: Quantitative and Qualitative Study - Özkan Gökhan; Yasin Yağmur Köksal; Okyay Pinar (Balkan Stomatological Society, 2020)
Background/Aim: The aim of this study was to determine the development and distribution of denture-related oral mucosal lesions in patients using removable prosthesis by using quantitative and qualitative research methods.